OBSERVATIONS ON THE PRAWN FISHERY OF THE MANGALORE ESTUARY ON THE SOUTH-WEST COAST OF INDIA - Ramaurthy, S (Indian Journal of Fisheries, 2011)
The estimated annual prawn landing varied from 1.09 to 5.S4 tonnes, the peak period of the fishery ^ bfia&. November-February. The fishery showed an inverse relationship to rainfall in ali’’Q(g<;y||aÂ£S except in 1965-66.